Optimizing Public Speaking Skills to Enhance Marketing Competence of Vocational School Students in Kampung Ilmu - Silalahi, Ronald Maraden Parlindungan; Suyoto , Yohanes Totok (STMIK Widya Cipta Dharma, 2025)
Public speaking is a critical communicative competency in the contemporary era, functioning not only as a component of personal development but also as a strategic element in marketing practices. The ability to deliver messages, ideas, or promotional content in a persuasive and structured manner plays a significant role in shaping audience perception and supporting business success. In response to this need, Pembangunan Jaya University is implementing a community service program in the form of public speaking skills training for Tegalwaru Vocational High School (SMKN) students. This initiative aimed to enhance students communication capacities in alignment with current industrial and professional demands. The training addressed both technical and practical dimensions of public communication, including effective speaking techniques, confidence building, appropriate use of body language, vocal intonation control, and strategies for designing and delivering engaging presentations. Additionally, participants were equipped with skills to respond to audience questions in a professional and composed manner. This activity is expected to foster practical competencies that will improve students readiness to face the challenges of the workforce and compete within increasingly dynamic and competitive labor markets. Moreover, the program reflects the tangible contribution of higher education institutions to human resource development through community-based empowerment initiatives, particularly those grounded in 21st-century skill development.